2015
DOI: 10.1038/srep15171
|View full text |Cite
|
Sign up to set email alerts
|

Fructose 1,6-bisphosphate, a high-energy intermediate of glycolysis, attenuates experimental arthritis by activating anti-inflammatory adenosinergic pathway

Abstract: Fructose 1,6-bisphosphate (FBP) is an endogenous intermediate of the glycolytic pathway. Exogenous administration of FBP has been shown to exert protective effects in a variety of ischemic injury models, which are attributed to its ability to sustain glycolysis and increase ATP production. Here, we demonstrated that a single treatment with FBP markedly attenuated arthritis, assessed by reduction of articular hyperalgesia, joint swelling, neutrophil infiltration and production of inflammatory cytokines, TNF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 47 publications
0
35
0
3
Order By: Relevance
“…The counterintuitive scenario that sluggish instead of hyperactive glycolytic flux feeds inflammatory activity has been confirmed in animal models of arthritis [32]. Replenishing the product of PFKFB3, fructose 1,6-bisphosphate (FBP) provided strong anti-inflammatory effects in vivo, compatible with the concept that enhancing glycolytic breakdown improves T-cell function and prevents pro-inflammatory effector functions.…”
Section: Ra T-cells – Energy-deprived T-cells With Impaired Redox Sigmentioning
confidence: 89%
“…The counterintuitive scenario that sluggish instead of hyperactive glycolytic flux feeds inflammatory activity has been confirmed in animal models of arthritis [32]. Replenishing the product of PFKFB3, fructose 1,6-bisphosphate (FBP) provided strong anti-inflammatory effects in vivo, compatible with the concept that enhancing glycolytic breakdown improves T-cell function and prevents pro-inflammatory effector functions.…”
Section: Ra T-cells – Energy-deprived T-cells With Impaired Redox Sigmentioning
confidence: 89%
“…Treatments with drugs increasing mitochondrial oxidation ( 9 ) or preventing FA synthesis ( 11 ) normalized the metabolism of these T cells, and decreased their infiltration into synovial tissue implanted in humanized mice. In the zymosan-induced model of arthritis, treatment with fructose 1,6-bisphosphate (FBP), the product of PFKFB3, attenuated disease severity ( 12 ). Lymphocytes infiltrating the joints of RA patients express a high levels of hexokinase HK2 , indicating that they are also highly glycolytic, which is consistent with their activation status ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that less macrophages infiltrated into the graft and the expression levels of TNF‐α appeared to be reduced in the FBP administration group. The anti‐inflammatory effect of FBP has been documented . The addition of FBP to the culture medium inhibited the release of TNF‐α and interleukin‐6 production in lipopolysaccharide‐exposed alveolar macrophages in the early phase of the inflammatory response , which suggest that FBP acts as a cytokine inhibitor and provides anti‐inflammatory effects.…”
Section: Discussionmentioning
confidence: 99%